ANALISIS FAKTOR YANG MEMPENGARUHI MANAJEMEN PAJAK DENGAN INDIKATOR TARIF PAJAK EFEKTIF (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2011-2012) - Iqbal Nul Hakim Darmadi; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2013)
This study examines and analyze the effect of firm size, capital structure (leverage), profitabilty, fixed asset intensity, inventory intensity and tax incentive to tax management using effective tax rates as a indicator. The sample of this study were 73 companies listed in Indonesian Stock exchange for years 2011-2012. Analysis tool used multiple linear regression with t test, F test, and test the coefficient of determination. The result show that there are negative effect of fixed asset intensity and inventory intensity on tax management. Another result show that there are positive effect of firm size on tax management. Capital structure (leverage), profitability and tax incentive were not shown to affect tax management.